THE USE NOUN PHRASE AND ADVERB PHRASE IN SENTENCE OF SIMPLE PAST TENSE ON RECOUNT TEXT - Wahyu Sulistya Pambudi (INFERENCE: Journal of English Language Teaching, 2022)
The purpose of the research is to describe and interpret the use of noun phrases and adverb phrases in simple past tense sentences in the recount text made by students of SMP IT Bunayya and SMP Permata Insani in Tangerang Regency. As many as 226 students as samples. The study took 10% of the total of 25 student writings. The method of this study used description analysis to describe and interpret recount text made by students. The results of this study concluded that; 1) Student errors in using of noun phrases in writing recount text found omission error as much as 78%, misformation error as much as 9%, addition error as much as 7% and misordering error as much as 4%. 2) Student errors in using of adverb phrases in writing recount text found omission error as much as 75%, addition error as much as 11%, misformation error as much as 6%, and misordering error as much as 7%. 3) The most dominant mistake of using noun phrases and adverb phrases made in omission error with a percentage as much as 75%